Synthesis and biological evaluation of novel 2-azido muramyl dipeptide as NOD2 agonistic adjuvants. (15th July 2022) - Reddy, Paturu Rama Subba; Sambyal, Shainy; Mhamane, Tukaram B.; Sravanthi, Vemireddy; Shafi, Syed; Khan, Imran A.; Sampath Kumar, Halmuthur M.
Graphical abstract: Abstract: Novel 2-Azido muramyl dipeptide was synthesized by the bio-isosteric replacement of the N -acetyl group of the muramic acid fragment with the azide functionality at the C2 position. In order to examine the effect of hydrophilic-lipophilic balance on the adjuvant activity, derivatives were synthesized by removing protecting groups sequentially to tune the polarity. Amongst five novel azido derivatives of MDP studied here, di- and mono-benzylated azido derivatives 10 and 11 exhibited good DENV specific antibody(IgG) response with Th1 polarization compared to parent compound Muramyl dipeptide (MDP) whereas all five new derivatives responded positively to NOD2 agonistic assays with compound 10 showing highest stimulation.